Firms’ exploitation of greenwashing in food packaging : Tactics and drivers of greenwashing in the food industry - Sippola, Roosa (My University, 2024)
The awareness of unsustainable consumption patterns and environmental challenges has led to an increased interest in environmentally sustainable purchasing decisions and green lifestyle. Nowadays, numerous firms aspire to spread an image of environmental friendliness and ecological consciousness to consumers in order to gain a competitive edge. This thesis focuses on the food industry, specifically the role of greenwashing in food packaging, as packaging is one of the major harmful forms of waste. The dissertation aims to understand the motivations behind consumers' intention to buy green products, the drivers of firms’ engagement in greenwashing, and the different tactics of greenwashing in food packaging. The main research question of this thesis is: "Why and how do firms practice greenwashing in food packaging?" To address this question, the thesis explores subquestions related to consumer behavior, motivations behind firms' engagement in greenwashing, and the tactics and strategies used by firms to exploit greenwashing. The findings of the thesis indicate that consumers are driven by values, environmental knowledge and concern, perceived quality as well as trust in farmers and firms when it comes to green food purchasing. Also, consumers buy green food out of habit and are influenced by green marketing. This ability to influence consumer behavior as well as competitive pressure motivates firms to appear green for consumers in order to leverage the growing green market. Firms are able to engage in greenwashing due to specific organizational and individual characteristics as well as lack of regulation. Firms exploit greenwashing through a variety of tactics. This thesis categorizes them into three: visual, verbal and labeling tactics. By addressing these topics, this thesis aims to offer valuable implications for firms, consumers, and policymakers, ultimately contributing to the discourse on sustainability and ethical business practices in the food industry.

Kasvava tietoisuus kestämättömistä kulutustottumuksista ja ympäristöhaasteista on lisännyt kuluttajien kiinnostusta ympäristöystävällisiin ostopäätöksiin ja vihreään elämäntapaan. Nykyään lukuisat yritykset pyrkivät luomaan ympäristöystävällistä ja ekologista imagoa kuluttajille saavuttaakseen kilpailuetua. Tämä kandidaatin tutkielma keskittyy elintarviketeollisuuteen, erityisesti viherpesun rooliin elintarvikepakkauksissa, sillä pakkaukset ovat yksi merkittävimmistä haitallisista jätteistä. Tutkielman tavoitteena on ymmärtää kuluttajien motiiveja ostaa vihreitä tuotteita, yritysten motiiveja viherpesuun sekä erilaisia viherpesutaktiikoita elintarvikepakkauksissa. Tämän tutkielman tutkimuskysymys on: "Miksi ja miten yritykset harjoittavat viherpesua elintarvikepakkauksissa?" Tutkimuskysymyksen tueksi käsitellään myös alakysymyksiä, jotka liittyvät kuluttajakäyttäytymiseen, yritysten viherpesun motiiveihin sekä yritysten käyttämiin viherpesun taktiikoihin ja strategioihin. Tutkielman johtopäätöksenä on, että kuluttajia ohjaavat vihreiden tuotteiden ostopäätöksissä arvot, ympäristötietoisuus, huoli ympäristöstä, koettu laatu sekä luottamus viljelijöihin ja yrityksiin. Lisäksi kuluttajat ostavat vihreitä elintarvikkeita tottumuksesta, ja heidän kuluttajakäyttäytymiseensä vaikuttaa vihreä markkinointi. Tämä kyky vaikuttaa kuluttajakäyttäytymiseen sekä kilpailupaineet motivoivat yrityksiä näyttäytymään ekologisena kuluttajille. Yritykset voivat harjoittaa viherpesua tiettyjen organisaatio- ja yksilökohtaisten ominaisuuksien avulla sekä lakisääntelyn puutteen vuoksi. Yritykset hyödyntävät viherpesua monin eri tavoin. Tämä tutkielma luokittelee ne kolmeen ryhmään: visuaalisiin, verbaalisiin ja sertifikaattitaktiikoihin. Tutkielma pyrkii tarjoamaan hyödyllisiä havaintoja ja johtopäätöksiä yrityksille, kuluttajille ja päättäjille, edistäen kestävyyden ja eettisten liiketoimintakäytäntöjen keskustelua elintarvikealalla.
Keywords: greenwashing, green food packaging, green advertising, green consumer behavior, viherpesu, vihreä elintarvikepakkaus, vihreä mainonta, vihreä kuluttajakäyttäytyminen